The 'question of possibilities' as a leitmotif for re‐imagining law for the 'Anthropocene'. Issue 5 (5th December 2022) - Mai, Laura
Abstract: The Anthropocene thesis, albeit not an unproblematic starting point, foregrounds the inadequacy of tacitly reproduced assumptions, theoretical dispositions, and conceptual repertoires which have supported a critical mass of legal thinking and praxis. Acknowledging the disruptive effects of the 'Anthropocene' for law, my aim in this article is to make explicit that re‐imagining law for the Anthropocene requires letting go of dominant ways of thinking and doing law, while enabling more adequate conceptions and modes of engagement to take hold. I suggest that the process of re‐imagining law for the Anthropocene requires navigating a space of continuity and break that demands the legal discipline to confront questions about disciplinary identity and responsibility. Reflecting on what the process of re‐imagining law might entail and how it could unfold, I propose the 'question of possibilities' as a leitmotif and ask: What could law become? In so doing, I map out concrete strategies and commitments which might inspire and encourage engagement with this question. These include: a practice of radical self‐reflection, the cultivation of a generative outlook, the acknowledgement of legal multiplicity, and a persistent commitment to meaningful change.